INTERACTING EFFECTS OF POST-WILDFIRE HYDROPHOBICITY AND VEGETATION RECOVERY IN A POOR FEN PEATLAND - MacKinnon, Brandon (My University, 2016)
To investigate the prevalence and magnitude of hydrophobicity in near-surface peat, a poor fen was characterized into four main post-fire microforms: i) severely burned hollows (SB-H), ii) severely burned Sphagnum fuscum hummocks (SB-Sf), iii) lightly burned S. fuscum hummocks (LB-Sf) and, iv) lightly burned feathermoss lawns (LB-F). The SB-H possessed the most hydrophobicity at the surface (85 ± 20 s) and increased at the 2 cm depth (183 ± 35 s). In comparison, the LB-F experienced an increase in hydrophobicity from the surface (44 ± 10 s) to 5 cm (323 ± 32 s) and remained high to the 10 cm depth (211 ± 31 s). Results on Sphagnum recovery show that only LB-Sf are recovering and the SB-H show marginal recovery of pioneer species such as Ceratodon purpureus and Polytrichum strictum. Moreover, S. fuscum had a mean surface cover of 56 ± 5.9% in the LB-Sf and both pioneer species together possessed a total cover of 15 ± 4.4% in the SB-H. While the vascular cover was correlated with increased transplant productivity which in conjunction with moisture availability (preference for hydrophilic substrate), transplant size (15cm diameter preferred over smaller colonies), and transplant location (SB-H preferred over LB-F) should all lead to decreased mortality in treatments. However, each species possesses slightly different characteristics that may be more desirable under reclamation conditions. Species that typically form hummock microform types like Sphagnum fuscum, Sphagnum magellanicum, and to some extent Sphagnum angustifolium can retain moisture under dry conditions (Clymo and Hayward, 1982; Andrus, 1986) and may be optimal for areas experiencing droughts or water limitations. Areas that are commonly inundated with water may benefit from a species that grows through lateral expansion such as Sphagnum angustifolium, Sphagnum riparium, or Sphagnum squarrosum (Andrus, 1986). With S. angustifolium possibly being the best generalist due to its ability to remain photosynthetically active throughout a large range of moisture contents, tolerate desiccation, and grow rapidly (Silvola and Aaltonen, 1984; Andrus, 1986).
Keywords: Sphagnum; Ecohydrology; Wildfire